2021
DOI: 10.1111/cwe.12396
|View full text |Cite
|
Sign up to set email alerts
|

Who Lost Most Wages and Household Income during the COVID‐19 Pandemic in Poor Rural China?

Abstract: China managed to eliminate all extreme poverty in rural areas in 2020. Poor households, however, may risk falling back into poverty due to the COVID‐19. This paper examines the impacts of the pandemic on wages and household incomes among different groups in poor areas of rural China. Using a unique dataset from five poverty‐stricken counties, we found that the pandemic has had large negative effects on wage income for migrant workers and workers in manufacturing, the private sector, and small enterprises. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, it is surprisingly observed that China's government had completely eradicated poverty in 2020, which is contrary to our simulation results. The inconsistency could be explained by the fact that the poverty alleviation policies implemented by China's governments are not considered after the pandemic outbreak [59].…”
Section: The Impact On Household Income and The Income Inequalitymentioning
confidence: 99%
“…However, it is surprisingly observed that China's government had completely eradicated poverty in 2020, which is contrary to our simulation results. The inconsistency could be explained by the fact that the poverty alleviation policies implemented by China's governments are not considered after the pandemic outbreak [59].…”
Section: The Impact On Household Income and The Income Inequalitymentioning
confidence: 99%
“…The COVID‐19 pandemic mainly occurring from 2020 to 2022 has had significant impacts on rural migrant workers in China. The pandemic has led to a decline in wages and household income for rural migrant workers (Long et al, 2021). Among the rural migrant workers, women were less likely than men migrants to return to the cities and also less likely to return to paid work after the pandemic outbreak (Song et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, these measures disrupted agricultural production and food chain supplies and increased the cost of food storage and transportation [67,68]. On the other hand, disruptions in the supply of agricultural products, restrictions on human movement, and suspension of transportation and passenger transport caused the agricultural and non-farm incomes of rural residents to be reduced [69]. Additionally, rural residents' expected income decreased when faced with epidemic-induced uncertainty, and they were more likely to upsurge precautionary saving motives as a result [70].…”
Section: Discussionmentioning
confidence: 99%